Isolation and structure of [HC[CH(SiMe(3))(SnMe(3))](2)](+): a remarkably stable sec-alkyl cation. - Schormann, M; Garratt, S; Hughes, D; Green, J; Bochmann, M (2002)
The reaction of the tin-substituted propene Me3Sn(R)CHCH=CHR (R = SiMe3) with MCl4 in dichloromethane in the presence of Me3SnCl gives the first examples of isolable sec-alkyl carbocation salts, [HC{CH(R)SnMe3}2]+M2Cl9- (M = Zr, Hf). The compounds are thermally stable and, unlike previously isolated trialkyl carbocations, do not require superacidic media or weakly coordinating anions for stability. The crystal structure and DFT calculations suggest polarization of the Sn substituents and hyperconjugation as the reason for the unexpected stability. The stabilizing effect of tin is significantly stronger than that of Si. The carbocations are effective initiators for the polymerization of isobutene, isoprene, and alpha-methylstyrene.